Coaching to strengthen critical success factors in integrative care for chronic fatigue patients: the Patient Needs-Resources Model - Araja, Diana; Krumina, Angelika; Nora-Krukle, Zaiga; Schneider, Marion E.; Berkis, Uldis; Murovska, Modra (Frontiers in Neuroscience, 2023)
Theoretical and empirical studies discover that an integrative approach is particularly important in chronic disorders and multiple long-term conditions, such as chronic fatigue. Chronic fatigue syndrome (CFS) is a classic example of a potentially severe, multisystemic illness with a wide diversity of symptoms and the corresponding diagnostic complexity. The prevalence of CFS-like syndromes expanded in the context of the COVID-19 pandemic, increasing the disorder and treatment burden. Thus, this article aimed to draw attention to the possibilities to strengthen the integrative approach to diagnosing and treating chronic disorders and multiple long-term conditions. The main critical success factors identified for integrative approaches were: a holistic approach, that provides a more comprehensive diagnostic and personalized treatment strategy, a multidisciplinary team, and patient engagement. The strengths and weaknesses of these factors were explored and coaching was identified as a potential unifying and reinforcing element. Coaching has a wide spectrum of manifestations clearly representing a holistic approach, that has been successfully used in multidisciplinary team building. Moreover, coaching exposes support addressing the patient engagement issues identified by the Patient Needs-Resources Model (PN-R Model) such as low levels of self-efficacy, optimism, and subjective well-being. Coaching may assist patients to identify and prioritize their goals, becoming aware of their personal resources, developing strategies for managing symptoms, and building skills to increase their self-efficacy and active engagement in the treatment process. Therefore, the authors emphasize coaching as a perspective element of optimization of patient care, that requires additional theoretical and long-term empirical research.